Modeling of heavy vehicle braking related to accident reconstruction for a range of vehicle and road characteristics / Mahdieh Zamzamzadeh - Mahdieh , Zamzamzadeh (2020)
In today's heavy-vehicle accidents, one of the major contributors is emergency braking, particularly for vehicles without an anti-lock braking system (ABS), which is dominant in developing countries like Malaysia. As the heavy vehicle driver applies emergency braking, there is a high chance of wheel lock-up, at which point the vehicle will skid along the road, creating braking marks from the tires. These braking marks are often used in crash reconstructions. Braking marks are mainly used by investigators to examine the vehicle's pre-impact velocity. There are many models and formulations based on kinetic energy that show the effect of some parameters. Still, there has been less discussion about vehicle dynamics' and loading condition's effects on slip ratio and wheel lock-up. This study used a multi-body dynamics method to examine the braking process in emergency braking for a better understanding of the characteristics of heavy vehicle braking, the performance of heavy vehicles during emergency braking, wheel lockup, and skidding as evaluated by the critical pedal force that triggers wheel lock-up, PFcrit. The findings generated from this study indicated that a minimum pedal force exists regardless of the factors involved. This inadvertently creates the PFcrit, which causes wheel lock-up and skidding. With that in mind, this study also highlighted the importance of PFcrit. Two phases were involved. The first phase examined PFcrit. Here, the wheel lock-up data for various pedal forces of the heavy vehicle's loading condition, its speeds, and the road surface conditions were generated through a multi-body dynamic model. Then the parameters that have a significant effect on the heavy vehicle's wheel lock-up were validated through statistical analysis. The results showed that the vehicle's dynamic characteristics could change during emergency braking situations, particularly for overloaded vehicles. This change can affect the heavy vehicle's wheel lock-up and the ability to stop safely. These parameters are fundamental, and so should be considered when determining braking marks distances. The most important finding to be noted from this study is the difference detected in the skidding distance when the vehicle's gross vehicle weight (GVW) is changed. The second phase of this study concentrated on the skidding distance and whether there is a contributory relation between skidding and vehicle dynamics. An alternative model was developed and then subjected to various vehicle characteristics and road conditions for this purpose. The primary consideration for developing the new regression model was to look at how vehicle dynamics and road conditions may impact the wheel lock-up and skidding distance. A nonlinear model to estimate the skidding distance. This model was derived as a case study by considering the nonlinear effect of the vehicle loading condition, tire forces, and longitudinal tire slip. According to the data presented here, this model provides information on how heavy vehicle GVW affects vehicle performance during emergency braking.